Internalization of Character Values within the Frame of Religious Moderation in Students with Intellectual Disabilities - Kirani, Cahya; Saidah, Nur; Gumilang, Ahmad Naufal (Indonesian Values and Character Education Journal, 2023)
This research is motivated by the urgency of creating equality in the context of religion for students with intellectual disabilities who have been marginalized. Character values within the frame of religious moderation are important to internalize in intellectually disabled children as well. Even though they experience delays in learning. This study aims to analyze the process of applying values to students with intellectually disabled and the application of instilling values to them and teachers. The research was carried out using a qualitative descriptive approach with data sources in the form of documentation, interviews, and observations which were then analyzed using the Miles and Huberman data analysis model to obtain in-depth results. This research found that: instilling character values is based on indicators of religious moderation in the form of national commitment by implementing nationality-based school activities, tolerance is taught through habituation, and non-violence by being aware of mistakes and accommodating. towards local culture by organizing various cultural events. Implicitly increasing teacher creativity in implementing learning and strengthening collaboration with parents. So, it can be concluded that students with intellectual disabilities (mild and moderate categories) can internalize character values of religious moderation.